The seed : finding purpose and happiness in life and work - Gordon, Jon, 1971- (Hoboken, N.J. : Wiley, 2011)
'A business fable to help you discover your purpose in work and lifeNew from Jon Gordon, the international and Wall Street Journal bestselling author of The Energy Bus, The Seed takes you on a quest for the meaning and passion behind work. Josh, an up-and-comer at a leading technology company, is disenchanted with his job. Challenged by his boss to take two weeks to decide if he really wants to work there, Josh takes off for the country, where he meets a wise farmer who gives him a seed and a promise: find the right place to plant the seed, and his purpose will be revealed.Through Josh's journey cross-country journey, you'll find surprising new sources of wisdom and inspiration in your own business and life. When he discovers where and how to plant the seed, you'll get a new sense of what it means to live and work with passion and purpose. Offers practical wisdom on discovering your true purpose, professionally and in life in general A business fable by Jon Gordon, the bestselling author of The Energy Bus and Soup Nobody captures the deeper meaning of business like Jon Gordon, and The Seed is his most searching and significant book yet. Whatever your profession, take this insightful look at the purpose behind work, and plant The Seed of inspiration in your life!'--
Keywords: Work -- Psychological aspects; Conduct of life; Inspiration